Global burden and temporal trends of tuberculosis attributable to high sugar-sweetened beverage consumption: insights from the Global Burden of Disease Study 2021 - Qiu, Lijie; Zhang, Yixiang; Yan, Kun; Xu, Jianxiu; Fan, Luxin; Peng, Mengmeng; Gao, Chengpeng (Frontiers in Nutrition, 2025)
BackgroundThis study aims to assess the current global burden and temporal trends of tuberculosis (TB) attributable to high sugar-sweetened beverage (SSB) consumption, and to analyze its association with the Socio-demographic Index (SDI), in order to provide evidence for TB prevention and control strategies.MethodsBased on data from the Global Burden of Disease Study 2021 (GBD 2021), we analyzed changes in incidence, prevalence, disability-adjusted life years (DALYs), and mortality of TB attributable to high SSB consumption globally and across regions from 1990 to 2021. The Das Gupta decomposition method was applied to assess the contributions of population growth, aging, and epidemiological changes.ResultsIn 2021, global disability-adjusted life years (DALYs) and deaths due to TB attributable to high SSB consumption increased by 52 and 44%, respectively, compared to 1990. However, the age-standardized rates (per 100,000 population) declined. The burden was highest and grew most rapidly in low-middle SDI regions, while high SDI regions experienced the fastest decline in mortality rates. The disease burden peaked in the 50–54 age group and was higher in males than females. Cross-country inequality analysis indicated that the TB burden was more concentrated in lower SDI regions.ConclusionThe health burden of TB attributable to high SSB consumption presents complex global patterns. Low- and middle-income regions face higher TB risks, highlighting the need for strengthened public health measures, particularly interventions targeting high SSB consumption, to achieve the goal of ending the TB epidemic by 2030.